Melting of large Pt@MgO(1 0 0) icosahedra. (2nd March 2017) - Rossi, K; Ellaby, T; Paz-Borbón, L O; Atanasov, I; Pavan, L; Baletto, F
Abstract: On the basis of ab initio calculations, we present a new parametrisation of the Vervisch–Mottet–Goniakowski (VMG) potential (Vervisch et al 2002 Phys. Rev . B24 245411 ) for modelling the oxide–metal interaction. Applying this model to mimic the finite temperature behaviour of large platinum icosahedra deposited on the pristine MgO(1 0 0), we find the nanoparticle undergoes two solid–solid transitions. At 650 K the 'squarisation' of the interface layer, while a full reshaping towards a fcc architecture takes place above 950 K. In between, a quite long-lived intermediate state with a (1 0 0) interface but with an icosahedral cap is observed. Our approach reproduces experimental observations, including wetting behaviour and the lack of surface diffusion.